Exploring environmental history [ selected essays - Smout, T. C. [ (T. Christopher)] (Edinburgh : Edinburgh University Press, 2009)
This volume brings together the best of T. C. Smout's recent articles and contributions to books and journals on the topic of environmental history.
1. The Environmental Historiography of Britain -- 2. The Highlands and the Roots of Green Consciousness -- 3. Exploiting Scottish Semi-natural Woods, 1600-1990 -- 4. The Pinewoods and Human Use, 1600-1900 -- 5. The Atlantic Oakwoods as a Commercial Crop in the Eighteenth and Nineteenth Centuries -- 6. Bogs and People in Scotland since 1600 -- 7. Energy Rich, Energy Poor: Scotland, Ireland and Iceland, 1600-1800 -- 8. Improvers and the Scottish Environment: Soils, Bogs and Woods -- 9. Trees as Historic Landscapes: from Wallace's Oak to Reforesting Scotland -- 10. The Alien Species in Twentieth-Century Britain: Inventing a New Vermin -- 11. Modern Agriculture and the Decline of British Biodiversity -- 12. History, Nature and Culture in British Nature Conservation -- 13. Environmental Consciousness
Description based on print version record
Includes bibliographical references (p 233-237) and index
Keywords: Human ecology -- History; Human ecology -- Scotland -- History; Human ecology